An ethical analysis of the implementation of poverty reduction policies in South Africa and Chile and their implications for the Church - Kretzschmar, Louise (HTS teologiese studies, 2014)
The focus of this contribution is the issue of poverty reduction within the South African and Chilean contexts. It is rooted in the academic field of Christian Ethics and also draws on several texts from the human and economic sciences. Policies adopted and practical steps taken to overcome poverty by the respective governments between 1990 and 2012 are evaluated and the theological and practical implications of poverty for the church are briefly highlighted. Despite differences between these two countries, South Africans can learn much from the Chilean policy and its implementation.